Talks on a sustainable fashion and textile system: a qualitative analysis on stakeholders (ModaPalavra e-periódico, 2022)
One of the many ways to describe the Italian fashion system, is the one that defines it as the action and interaction of people in the process of making: on their artifacts, knowledge, expertise relies the essence and the engine of the fashion industry. In the contemporary time, driven by the shift towards sustainability, designers areworking together with farmers, raw material processors, artisans, garment makers, manufacturers, retailers, and the more they are involved in and familiar with them, the more they can intervene to bring change and innovation towards a better and sustainable future. Suppliers are the places where sustainability happens, and moreover, with their decades-long efforts, precious resources to learn from.The article reports a qualitative investigation on the Italian fashion supply chain, with the aim to detect the hot spots where human interaction among manufacturers and designers is fostering sustainable practices, processes, products.
Keywords: Sustainability; Manufacturers; Interaction